Comprehensive Analysis of the Level of Knowledge, Stigma in an HIV/AIDS Program - Elisabeth Purba, Ivan; Rohana Sinaga, Taruli; Adiansyah, Adiansyah (International Journal of Science, Technology & Management, 2023)
The number of HIV/AIDS infections in Indonesia tends to rise year after year, although it is clear that in recent years, the incidence has peaked and is highest among those between the ages of 20 and 49. primarily through the promotion of socialization and health education, to lessen the rate of HIV/AIDS transmission. This study intends to understand and evaluate people's attitudes and knowledge towards HIV/AIDS prevention in 2022. This study employed a one-group, pre-and post-test quasi-experimental design. There were as many as 33 samples collected. There was a statistically significant difference in the average increase in knowledge score about HIV, according to the study's results utilizing the Paired t-test, which had a P-value of 0.01.